2011
DOI: 10.3892/ijmm.2011.783
|View full text |Cite
|
Sign up to set email alerts
|

Novel GATA4 mutations in lone atrial fibrillation

Abstract: Abstract. Atrial fibrillation (AF) is the most frequent cardiac arrhythmia and is a major cause of morbidity and mortality. Previous studies have established genetic defects as a risk factor for AF in a minority of patients. However, AF is of substantial genetic heterogeneity and the molecular determinants for AF in a majority of cases remain unclear. In this study, the entire coding sequence and splice junctions of GATA4, which encodes a zinc-finger transcription factor essential for cardiogenesis, were seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…A growing body of evidence indicates that genetic factors are significant in the pathogenesis of lone AF and familial AF (24), with our previous studies indicating a genetic predisposition in familial AF (2,5). However, the mechanism underlying this disorder remains unclear.…”
Section: Introductionsupporting
confidence: 50%
“…A growing body of evidence indicates that genetic factors are significant in the pathogenesis of lone AF and familial AF (24), with our previous studies indicating a genetic predisposition in familial AF (2,5). However, the mechanism underlying this disorder remains unclear.…”
Section: Introductionsupporting
confidence: 50%
“…Here we report 9 rare variants out of which 5 Table S3). Our study along with other existing reports suggest that the frequency of GATA4 mutations is more in N-terminal transactivation domain despite of the fact that zinc finger DNA-binding domain of GATA4 is critical for GATA4 function (Butler et al, 2010;Jiang, Shen, Fang, Liu, & Yang, 2011;Tomita-Mitchell et al, 2007;Yang & Gharibeh, et al, 2013;Yang & Li, et al, 2012;Zhang et al, 2008). Several of these studies have also demonstrated functional impairment of GATA4 caused due to mutations in this region Yang & Li, et al, 2012;Wang, Sun, & Yang, 2012;Yang & Gharibeh, et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
“…1315 In addition, mutations in several transcription factors involved in atrial development have also been identified in patients with lone AF. 1618 Yet the influence of these variants is complex: for instance in one example, two different alleles of the same SNP are associated with increased AF risk. 19, 20 Supplemental Table S1 provides a comprehensive list of AF associated rare variants or mutations that have been reported to date.…”
Section: The Role Of Rare Genetic Variants In Afmentioning
confidence: 99%